ENERGY EFFICIENCY ANALYSIS IN MOBILE HYDRAULICS - Ervin Strmčnik; Damjan Konovšek (Journal of Energy Technology, 2024)
The primary purpose of this paper is to estimate possible energy and cost savings in the optimization of mobile hydraulics. A gerotor is a low-speed, high-torque hydraulic motor, which is very rarely described in the literature and often use in mobile hydraulics. In this paper, the total efficiency of the hydraulic motor was investigated. The influence of the size of the holes in the valve plate on the total efficiency of the gerotor was analysed. The total efficiency is the most important and prominent information about the energy conversion of hydraulic components, such as hydraulic motors and pumps. The operation of a gerotor is briefly described as well as some equations for the determination of displacement and efficiency. The results show that there is a correlation between the size of holes in the valve plate and the total efficiency of the gerotor. Furthermore, a very high total efficiency was obtained with the hole size of Φ6.3 mm. In that case, the total efficiency was on average 16.1% higher in comparison to the total ef- ficiency when the hole size was Φ5.5 mm. It plays a significant role in possible reductions in energy cost. Energy analysis and cost estimation were conducted.